Heavy-to-light semileptonic decays of Λb and Λc baryons in the covariant confined quark model - Gutsche T.; Ivanov M. A.; Korner J. G.; Santorelli P.; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich (2014, 2014)
Title screen